Modern Didactic Text in Russian: Mechanisms of Perception and Principles of Construction (Филологический класс, 2020)
The article is devoted to the study of cognitive mechanisms of perception of textual information: stages and peculiarities of its intellectual processing and its understanding and internalization in the light of the activity-based theory of cognition. The author analyzes the existing approaches to the definition of the essence of the modern didactic text, which is not to focus on memorizing concepts, but on the development of independence and creative attitude to learning. This requires a fundamentally new approach to the structure of the textbook as a whole and its individual sections (themes) in particular, taking into account the psychological laws of information acquisition and specific features of formation of cognitive and metacognitive operations of the child. Special attention is given to psycholinguistic methods and techniques of identification of the nature of reception of the didactic text in the unity of its formal and content parameters. The article poses a postulate about the need to take into consideration these mechanisms in the process of design (development) of a didactic text in Russian for students of secondary general education institutions. The didactic text is analyzed from two angles: 1) from the standpoint of the person reading (listening to) the text and modeling the image of the content of the text perceived in their mind; 2) from the standpoint of the author of the text. The article contains experimental data, which make it possible to identify the factors that determine the nature of perception of the didactic text. The author concentrates her attention on individual psychological differences of information perception both via verbal and non-verbal codes and specificity of acquisition of information presented in different ways (in particular, by way of algorithms or equivalents). The author’s analysis of typical exercises and tasks (including after-reading tasks), which can be found in modern textbooks of the Russian language, in terms of their cognitive “comfort” and efficiency for children with different lateral profiles is methodologically important. The study reveals the factors facilitating perception and understanding of the learning material or hindering these processes. The research results include a practical guide for teachers-philologists, specialists in methods, and psycholinguists regarding the form and the content of didactic texts (including game-based ones) for teaching Russian.